ENVIRONMENTAL COMMUNICATION PATTERNS BASED ON LOCAL WISDOM IN MANAGEMENT OF LUBUK LARANGAN IN SUBAYANG RIVER - Yasir Yasir; Muhammad Firdaus; Rusmadi Awza (Sosiohumaniora, 2023)
Lubuk larangan is tradition and also a means of communication based on local wisdom in managing the river and forest environment in Kampar Kiri Hulu District, Kampar Regency. This study aims to explain environmental communication pattern based on local wisdom in the management of Lubuk larangan in the Subayang River, Kampar Regency. This study uses a qualitative descriptive research method using an interactive model. There were six informants who were selected purposively. The results show that environmental communication is based on the local wisdom of the community that has been passed down from generation to generation. Traditional leaders (ninik mamak) play an important role in conveying messages of environmental concern in preserving the preservation of the forbidden pits (lubuk larangan), rivers and forest. This hereditary tradition forms local wisdom as a form of joint action through deliberation and mutual cooperation activities. The community manages the lubuk prohibition through communication based on customary law, rituals, myths, phrases, proverbs, and the annual tradition of catching fish (mencokou). This channel of communication through customary laws, myths and traditions is very effective in conserving the Subayang river and forest areas. The environmental communication based on local wisdom in the Subayang River contributes to supporting the preservation of natural resources of forests, rivers, fish and existing ecosystems. Stakeholders such as local governments, universities, mass media, NGOs, companies and the community must synergize with each other in developing local wisdom as a tourist area so that it can be of added value.